INFLATION DYNAMICS IN THE USA AND EU: VAR ANALYSIS AND FORECASTING - Cicmil, Danica (International Journal of Economic Practice and Policy, 2024)
This paper aims to analyze the relationship between the inflation rate in the USA and the inflation rate in the EU and to make short-term forecasts of their future movements. The Vector Autoregression (VAR) model was used to study the dynamic relationships among multiple variables. The VAR model was fitted on the data with a maximum lag of 5, and the diagnostic checks were performed to ensure it was correctly specified. The results are presented and discussed and the paper concludes by suggesting that future research should focus on addressing the problem of non-stationarity in the residuals and on testing the robustness of the model.
Keywords: VAR; inflation; forecastig